Strategi Modal Politik Bourdieu dalam Kemenangan Andi Sumangerukka Pada Pilkada Sulawesi Tenggara 2024 - Muhammad Raihan Kamal; Ariana Yunus; Sakinah Nadir; Ismail Dwi Saputra (Universitas Muhammadiyah Sorong, 2026)
This study is motivated by the victory of Andi Sumangerukka in the 2024 Southeast Sulawesi Regional Head Election despite not being a native figure genealogically or culturally. This study aims to analyze Andi Sumangerukka’s winning strategy through the use of political capital in local political contestation. The research employs a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The findings reveal that Andi Sumangerukka’s victory was influenced not only by economic strength, but also by his ability to build social networks, utilize digital media, adapt local cultural symbols, and establish a strong leadership image within society. In addition, the study found a shift in the political orientation of Southeast Sulawesi society from identity-based politics toward more rational considerations of candidates’ capacity and leadership quality. The study concludes that the effective management of various forms of political capital plays an important role in winning local political contestation.